2016
DOI: 10.1007/s13304-016-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oncological outcomes: comparison of the conventional and minimally invasive esophagectomy, a single institution experience

Abstract: Minimally invasive esophagectomy is becoming the routine procedure for resectable esophageal cancer. The aim of this retrospective study is to analyze the oncologic adequacy of these two procedures at our Centre. Out of 1252 registered esophageal cancer patients at our institute from 2006 to 2015, 206 patients who underwent a surgical resection with curative intent and a complete medical record were retrospectively evaluated thru hospital medical record system (HIS). Patients were allocated into the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although promising progress has been attained in treating esophageal cancer, it responds poorly to chemotherapeutic drugs and the mortality still remains high [ 51 , 55 , 56 , 57 , 58 , 59 ]. Surgery, chemotherapy and radiotherapy are the most widely-used treatment methods but about half of advanced esophageal cancer cases result in recurrence and patients normally succumb to resistant disease [ 60 , 61 , 62 , 63 , 64 ]. There is a lack of understanding of the mechanisms driving the initiation, progression and the occurrence of refractory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although promising progress has been attained in treating esophageal cancer, it responds poorly to chemotherapeutic drugs and the mortality still remains high [ 51 , 55 , 56 , 57 , 58 , 59 ]. Surgery, chemotherapy and radiotherapy are the most widely-used treatment methods but about half of advanced esophageal cancer cases result in recurrence and patients normally succumb to resistant disease [ 60 , 61 , 62 , 63 , 64 ]. There is a lack of understanding of the mechanisms driving the initiation, progression and the occurrence of refractory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, MIE and OE have been demonstrated to have comparable feasibility, safety, and oncologic efficacy [6][7][8][9][10][11][12], and the benefits of thoracoscopic esophagectomy have gradually been accepted with continuous improvements in relation to surgical instruments and skills required for the procedure. Palazzo et al [12] found that MIE was better in survival compared to hybrid Ivor Lewis esophagectomy or OE; however, differences between the outcomes of hTE and cTLE, the two most commonly performed MIE procedures, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established over the past two decades that the feasibility, safety, and oncologic efficacy of MIE and OE are comparable [6][7][8][9][10][11][12]. However, possible differences in short-and long-term outcomes between hMIE and cTLE for ESCC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Less invasive surgical resection techniques can be considered. In a retrospective study comparing conventional open esophagectomy (OE), minimally invasive esophagectomy (MIE), and Hybrid esophagectomy, there was no significant difference between the three techniques for the outcomes of lymph nodes retrieved, resection margin-positive disease, and tumor recurrence (82).…”
Section: Treatment and Managementmentioning
confidence: 99%